Aspidistra cleistantha, a new species of Asparagaceae from Guangxi, China - Nong, Dong-Xin; Huang, Xue-Yan; Huang, Bao-You; Lü, Hui-Zhen (Phytotaxa, 2018)
A project aimed to investigate and monitor the Chinese Materia Medica raw material resources for national essential drugs has been conducted in Guangxi Zhuangzu Autonomous Region, China since 2012. During the study, some unknown plants were brought into cultivation for further research. These plants constantly flowered in the following years, among which more than 30 Aspidistra Ker Gawler (1822: 628) species. They have been identified after studying relevant literature in China and neighbouring countries (Averyanov & Tillich 2014, Li & Lin 2016, Liang & Tamura 2000, Liang et al. 2016, Lin et al. 2015a, 2015b, Nguyen et al. 2017, Tillich 2005, 2006, 2008, 2014, Tillich & Averyanov 2012, Vislobokov 2016, Vislobokov et al. 2016, 2017). In the present paper, we describe a new species of Aspidistra from limestone mountains, southern Guangxi, namely Aspidistra cleistantha.